Customer behaviour change through gamification: Goal Framing and Temporal Effects - Nortje, Jacqueline (University of the Witwatersrand, Johannesburg, 2024)
Gamification is a widely used design strategy deployed across a range of contexts to encourage individuals to participate in key behaviours. Gamification deploys a range of mechanics typically associated with games to leverage underlying behavioural dynamics. A frequently used game mechanic is the use of goal setting, where these goals are either explicit aspects of the game or implicit through other game mechanics. Despite the widespread use, and continuous growth, of gamification there are aspects that are poorly researched or insufficiently grounded in theory. This thesis investigates two such aspects of gamification: the use of goal setting and the use of gamification over extended periods of time. The thesis aims to answer the research question: Does framing impact the success of goal setting in gamification design, and what is the long-term effect of such a gamification design on behaviour change and performance? This thesis consists of four related papers that addresses this question. According to goal setting theory, goals that are specific and challenging, while still being achievable, are more successful at driving positive outcomes compared to easy goals (i.e., where the goal is easily attained with little or no additional effort) or no goals at all. Furthermore, goal setting theory describes four moderators that impact how successful a goal may be, namely, ability, task complexity, goal commitment and feedback. Focusing on ability (measured as self-efficacy) and task complexity (measured as motivation), research typically describes two types of goal framing approaches and when each would be most appropriate. In this context, “framing” refers to how the goal is positioned or worded and on the focus are of the underlying goal. Performance framing is most appropriate when self- efficacy is high, or task complexity is low. Learning framing is most appropriate when task complexity is high, or self-efficacy is low. Despite the distinction between performance framing and learning framing within goal setting, performance framing tends to be the predominant choice in practice, even when there are indications that a learning-framed approach would be more suitable. Furthermore, little research exists on the appropriate framing approach when considering the interaction between the moderators. Paper 1 presents a literature review of goal setting theory and introduces an alternative model for improved goal framing within a gamification design framework that formalises the recommended framing approach based on an individual’s underlying psychological states. The model also introduces a novel hybrid approach to goal framing to accommodate scenarios where an individual has higher levels of self-efficacy with lower levels of motivation, and vice versa. Paper 2 presents a quasi-experimental field experiment that tests the various framing approaches based on an individual’s self-efficacy and motivation at the onset of the experiment. The experimental case site was Vitality Active Rewards, a gamification platform that is part of Discovery Vitality, a wellness program in South Africa. The targeted behaviour in this study is physical activity as measured through the gamification platform. The researcher grouped study participants based on their self-efficacy and motivation using ii latent profile analysis and deployed a difference-in-differences analysis to assess the effects of the framing conditions within each group. Notably, each framing condition was successful at improving physical activity in at least one group and the researcher was able to refine the proposed optimal framing following the results of the field experiment. When considering the broader gamification design framework, despite the prevalence of gamification as a design strategy, little research or documentation of the long-term effects is available. Studies tend to be over shorter periods and there is some scepticism about whether gamification can be used in the long-term or if results are purely due to the novelty of the initial design. Furthermore, gamification design is seldom grounded in theory, leading to a somewhat fragmented view of the field. Paper 3 presents a literature review of gamification design and expands on the model introduced during the goal setting portion of the study to consider various scenarios with the intent of better understanding the effects of time on the efficacy of gamification design. The researcher provides a recommendation for the optimal approach to ensuring that a gamification platform may have longer lasting effects on the targeted behaviour. Finally, Paper 4, presents a mixed methods case study that evaluates the key propositions from the model against the Vitality Active Rewards gamification platform. Vitality Active Rewards has been live since September 2015 and underwent two major updates since its deployment. The platform presents a rich source of secondary data as well as the opportunity to conduct qualitative research in a novel population represented by financial advisors. The research highlights the initial positive effects of gamification on a target variable followed by the inevitable decline over time once the novelty of the intervention wears off. Furthermore, the study investigates the effects of making changes to a gamification platform over time and provides a recommendation for practitioners on how to approach these changes in a way that will ensure the longevity of the platform. The thesis makes several key contributions to both fields of gamification design and goal setting theory. Firstly, it enhances the use of goal setting theory within a gamification context through an alternative framing methodology. Additionally, the thesis delivers theoretical insights, elucidating the long-term impact of gamification on behaviour change and performance. The study provides a methodological contribution to gamification design by presenting an alternative implementation of gamification design strategies to ensure efficacy over time. Furthermore, the research contributes empirically by providing an understanding of the lasting effects of gamification on behaviour change and performance by examining an existing intervention that has been successful over an extensive period.
A research report submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Gamification; Temporal effects; Goal setting theory; Goal framing; Behaviour change; SDG-8: Decent work and economic growth